High molar mass amphiphilic block copolymer enables alignment and dispersion of unfunctionalized carbon nanotubes in melt-drawn thin-films. (3rd October 2017) - Arras, Matthias M.L.; He, Bojia; Jandt, Klaus D.
Abstract: To extensively control the nanofiller arrangement (location, orientation, shape) is still a bottleneck for multi-wall carbon nanotube (MWCNT) nanocomposites. Here, we demonstrate simultaneous control of alignment (orientation) and dispersion (location) of pristine, i.e., unfunctionalized MWCNTs using a high molar mass (HMM) amphiphilic block copolymer (BCP). We tested whether a HMM BCP in a selective solvent (i) disperses MWCNTs (ii) disperses MWCNTs by similar mechanisms to low molar mass BCPs and (iii) is melt-drawable to align the well dispersed MWCNTs. The dispersibility of MWCNTs within poly(styrene)- block -poly(2-vinylpyridine) (PS- b -P2VP) ( M ¯ w ≈ 500 kg / mol ) and its homopolymers in (non-)selective solvents was investigated by sedimentation experiments, transmission electron microscopy and visible/near-infrared spectroscopy. Through BCP micelle mediated steric stabilization, HMM PS- b -P2VP led to a highly stable MWCNT dispersion, which is explained in two simple graphical models. Using the melt-drawing technique, the well dispersed MWCNT/PS- b -P2VP dispersion was processed into a nanocomposite with a high degree of MWCNT alignment and dispersion. HMM BCPs are of significance for structural MWCNT/polymer nanocomposites, typically containing HMM polymers. Graphical abstract: Highlights: High molar mass block copolymer (BCP) disperses multi-wall carbon nanotubes (MWCNTs) well and stable. High molar mass BCP is suitable for simultaneous MWCNT alignment and dispersion in thin-films. Evidence that poly(2-vinylpyridine) interacts well with MWCNT and, thus, as part of a BCP is very effective in dispersing.